The gift of democracy: a Tibetan experience with democracy in exile - Tenzing Palmo (European Bulletin of Himalayan Research)
Instituting democracy was one of the foremost engagements of the Dalai Lama in exile. The intricate connection drawn between democracy, the nationalist goal and the Dalai Lama gives a unique flavour to Tibetan democracy. Considered as a ‘gift’, democracy is conferred a sacred character by the Tibetan people which immunises it from the usual aspects of everyday democratic functioning of which discussion, dialogue, differences and dissent are an integral part. Drawing on theoretical concepts from the anthropological literature on democracy, gift and the public sphere, and putting them in conversation with the primary data obtained from field research, this paper first examines the complex relationship between democracy and Tibetan nationalism, and how democracy came to be constituted within a nationalist rhetoric. It then shows the characteristics of a Tibetan public sphere considered as a source of trouble within the complex web of democracy and nationalism in exile.